Teatro-Escola Cláudio Barradas: a narrativa de um aluno de licenciatura em teatro sobre o aprendizado teórico-prático adquirido no teatro experimental da UFPA e nas vivências em sala de aula. - MEDEIROS, Neivaldo dos Santos (2022)
This research aim to present the report of experience of the trajectory of the theoretical-practical, academic and technical, learning of the student Neivaldo dos Santos Medeiros in the licenciad curse in theatre from march 2014 to December 2018. This work of conclusion of curse is a narrative study based on two pedagogical-artistic experiences at the Teatro Universitário Cláudio Barradas and at the curricular stage of the 7th and 8th semesters with the students of the theater class for children in this work approaches on the fourth century a. C. in Greece to the present day, with Margot Berthold, Cyro Del Nero and Gianni Ratto as references. Another author like Luís Cláudio Cajaíba is present in some approaches on the arrangements of stage and audience throughout history. In this research, we focus on the UFPA University Theater in its function as theater-school and cultural equipment in the city of Belém. A brief account of the scenographic production of the artist Claudio Bastos, the set designer responsible for inspiring this work, is present in this dissertation. As well as, to report the theatrical practice in the free curses of the Theatre and Dance School of UFPA, focusing on the difficulties and overcoming of the trainee-students in the planning and execution of the classes. The theatrical practices carried out with the students were adopted methodologies based on the works of Ricardo Japiassu, Viola Spolin and Mark Anby, with regard to improvisation for the theater.